2012
DOI: 10.1645/ge-2941.1
|View full text |Cite
|
Sign up to set email alerts
|

New Species and Geographical Records of Dactylogyrids (Monogenea) of Catfish (Siluriformes) from the Peruvian Amazonia

Abstract: Three new species of gill monogeneans (Dactylogyridae: Ancyrocephalinae) are described from siluriform catfish from Iquitos, Peru: Demidospermus mortenthaleri n. sp. from Brachyplatystoma juruense (Boulenger), Demidospermus brevicirrus n. sp. from Pimelodus sp., and Aphanoblastella aurorae n. sp. from Goeldiella eques (Müller & Troschel). Demidospermus mortenthaleri is characterized by a male copulatory organ (MCO) with a small loop at its middle portion; 2 types of hooks, of which pairs 5 and 6 are longer tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 25 publications
4
30
0
2
Order By: Relevance
“…5). Mendoza-Palmero et al (2012) reported the presence of expanded shank and highly reduced thumb of hooks of pair 7 for specimens of U. brittani from Pterygoplichthys anisits (Mendoza-Palmero et al 2012: Fig. 46).…”
Section: Discussionmentioning
confidence: 99%
“…5). Mendoza-Palmero et al (2012) reported the presence of expanded shank and highly reduced thumb of hooks of pair 7 for specimens of U. brittani from Pterygoplichthys anisits (Mendoza-Palmero et al 2012: Fig. 46).…”
Section: Discussionmentioning
confidence: 99%
“…Some specimens were mounted in Hoyer's medium for sclerotized structures observation, while others were stained with Gomori trichrome in order to study the internal structures. The parasites were identified according to Suriano et al (1986), Kritsky et al (2000), Mendoza-Franco et al (2007), Carvalho et al (2009) andMendoza-Palmero et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…The present study provides two new monogenean records for Mexico, Gyrodactylidae sp. and Unilatusunilatus , the latter belonging to the Dactylogyridae which was previously reported on the snow pleco P.anisitsi Eigenmann and Kennedy and on Plecostomus sp., from Brazil and Peru, respectively (Mendoza-Palmero et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, some specimens were mounted in a mixture of lactic-acid (LA) and glycerin- ammonium picrate (GAP) and then remounted in Canada balsam as permanent preparations (Mendoza-Franco et al 2013). Parasite identifications were made using a Leica microscope DM2500 with Nomarski interference contrast and based on descriptions provided in the following references: García-Vásquez et al 2007, 2015, Jogunoori et al 2004, Kritsky et al 1989, Lim 1996, Mendoza-Palmero et al 2012, Pariselle and Euzet 1995, Yamaguti 1963. Reference specimens were deposited in the National Helminthological Collection of Mexico ( CNHE ).…”
Section: Methodsmentioning
confidence: 99%